Pengaruh Pemberian BAP dan NAA terhadap Pertumbuhan Krisan (Chrysanthemum morifolium, Ram.) dalam Kultur Jaringan - Yohana Theresia Maria Astuti; Neny Andayani (Universitas Atma Jaya Yogyakarta, 2005)
The objective of this study was to evaluate the effect of combination benzyl amino purine(BAP) and naphtalene acetid acid (NAA) on tissue culture of Chrysanthemum. Theexperiment was conducted at The Tissue Culture Laboratory, Agriculture Faculty,Stiper Agriculture Institute. The Completely Randomized Design was applied in thisexperiment, consisting of two factors; those were BAP and NAA application. Each factorconsisted of four treatments. Each combination of treatment was carried out with ninereplications. The conclusion from this study were: Application of higher BAP and NAAconcentration increased budding of explant, whereas application of higher NAA thanBAP concentration increased the growth of bud and leaf number, also increased rootingof explant.